Hebrews - Schreiner, Thomas R. (Bellingham, WA : Lexham Press, 2020)
"Jesus' final cry on the cross-"it is finished"-captures the theology of Hebrews. Thomas R. Schreiner clarifies Hebrews's complex argument by keeping a sustained focus on its logical flow. He interprets Hebrews in light of its prominent structures of promise and fulfillment, eschatology, typology, and the relationship between heaven and earth. Schreiner probes the letter's unique theological contributions, such as its presentation of Jesus' divinity and humanity, his priesthood and sacrifice, the new covenant, warnings and exhortations, and the reward for those who persevere in Christ. The Evangelical Biblical Theology Commentary (EBTC) series locates each biblical book within redemptive history and illuminates its unique theological contributions. All EBTC volumes feature informed exegetical treatment of the biblical book and thorough discussion of its most important theological themes in relation to the canon-all in a style that is useful and accessible to students of Scripture"--
Minimal Level Cataloging Plus.
Includes bibliographical references (pages 501-517) and indexes.
Keywords: Bible. -- Commentaries; Commentaries